If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -1) = 9 + -1(y + 2) Reorder the terms: (-1 + X) = 9 + -1(y + 2) Remove parenthesis around (-1 + X) -1 + X = 9 + -1(y + 2) Reorder the terms: -1 + X = 9 + -1(2 + y) -1 + X = 9 + (2 * -1 + y * -1) -1 + X = 9 + (-2 + -1y) Combine like terms: 9 + -2 = 7 -1 + X = 7 + -1y Solving -1 + X = 7 + -1y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + X = 7 + 1 + -1y Combine like terms: -1 + 1 = 0 0 + X = 7 + 1 + -1y X = 7 + 1 + -1y Combine like terms: 7 + 1 = 8 X = 8 + -1y Simplifying X = 8 + -1y
| (3x-5)(3x-5)=x+25 | | 3b+7=2+b | | 15x^2-44x= | | sqr(log(x))+1=0 | | 2*x^2-(5-i)*x+6=0 | | 3x^3*5x^2= | | 3x*5x^2= | | x*5x= | | 1.5(n-1)=n+3 | | 1.5n=n+4 | | y^3-7y=0 | | 100-20y=-y^2 | | y^2-3y=3y-8 | | 6x^2-28x=-32 | | 2*(5x-3)-7*(x+2)=-5 | | y^2-3y=4 | | -3x+9=1 | | 5t^2-t=0 | | 5x-20x=60 | | 3-2x+5=6x | | 2-x=3x-4 | | 1.2x^2+x=0 | | x^4-8x^3-6x+12=0 | | 0.7x^2-x^3=0 | | 7x^2+20x-36=0 | | x+2=-4x-7 | | 10x+7+2x=16x+7 | | 2x-[3-5x(x-3)]=(2x-1)+10 | | (4-3(-2))x=-2x+2 | | x-7y=22 | | lnx-lnx(y-1)=1 | | x(4x-12)-7=-7 |